Skeletal muscle signaling response to concurrent endurance and resistance exercise - Makanae, Y.; Ogasawara, R.; Fujita, S. (The Journal of Physical Fitness and Sports Medicine, 2015)
Concurrent training, which is a combination of resistance exercise (RE) and endurance exercise (EE) performed in succession, is used to improve both muscle strength and cardiovascular function. Although numerous studies have investigated the effects of concurrent training on muscle adaptation, no consensus has been reached. Skeletal muscle adaptation is induced by the cumulative effects of the repeated cellular and molecular responses to an acute bout of exercise. Divergent exercise modes induce different molecular signaling responses depending on the muscle contraction type. It is well known that RE induces the mammalian target of the rapamycin complex 1 (mTORC1) signaling pathway while EE activates AMP-activated protein kinase (AMPK) signaling, and the signaling pathways stimulated by each exercise could interfere with each other. Thus, the inconsistencies in the effects of concurrent training on muscle adaptation may be explained by the different signaling interactions occurring in response to RE and EE. This review article describes the signaling pathways induced by RE, EE, and concurrent training.